The impact of comet assay data normalization in human biomonitoring studies outcomes. (10th October 2020) - Esteves, Filipa; Amaro, Raquel; Silva, Susana; Sánchez-Flores, María; Teixeira, João Paulo; Costa, Carla
Highlights: Assay controls may contribute to the reduction of inter-experimental variation in comet assay. Normalization strategies can influence the statistical results of a human biomonitoring study. Positive standards display a higher stability across experiments. Normalization with positive standards promote lower levels of data variation. Abstract: The comet assay has been extensively used in biomonitoring studies. To avoid intra-experimental variability, the incorporation of assay controls in each work session for data normalization has been suggested by some authors but has never been thoroughly analyzed. The aim of this study was to address the impact of data normalization in the results of a biomonitoring study using different normalization models. Human peripheral blood mononuclear cells (PBMC) from 140 healthy individuals were analyzed using the alkaline and FPG-modified version of the comet assay across seven different work sessions. In addition to negative standards, methyl methanesulfonate (MMS) and Ro 19−8022 plus light treated PBMC, were also included in the assay as positive standards. To verify the impact of data normalization, some demographic, lifestyle and environmental exposure-related variables were selected. Significant associations with independent study variables were observed using normalized comet endpoints, as opposed to raw data. After normalization, levels of DNA strand breaks were significantly higher among males and older individuals (>71 years), while net FPG-sensitive sites were positively related to smoking habits and environmental exposures (i.e. air pollution and bottled water consumption). This study highlights how the normalization strategies can influence the statistical results of a human biomonitoring study and lead to different data interpretations.